Some Types of Contra- gp- Closed Functions in Topological Spaces - Hammed, Dunya M; Salman, Mayssa Z (Al-Nahrain Journal of Science, 2018)
In this paper, we introduce a new type of contra- closed functions which is the contra-gp- closed functions, as well as we using this function to give and study other types of contra-gp- closed functions namely (contra-gp*- closed function, contra-gp**- closed function, contra-pre gp- closed function and contra-pre gp*- closed function) and find the relation between these functions. Also, we will proved several properties of these functions types.